Efektivitas Model Continuity Of Care Terhadap Kesiapan Ibu Menghadapi Persalinan - Rikaoctriantiaskar, Rikaoctriantiaskar; Iffah, Uliy; Rachim, Dyan Permata (Afiasi : Jurnal Kesehatan Masyarakat, 2026)
Introduction: Maternal readiness for childbirth is a critical indicator of successful labor outcomes. Maternal unpreparedness can lead to increased anxiety, impaired decision-making, and prolonged labor duration. The Continuity of Care (CoC) model, defined as midwifery care provided continuously from pregnancy to the postpartum period by the same healthcare provider, is believed to enhance maternal self-confidence, interpersonal closeness, and readiness for childbirth. Given these potential benefits, evaluating CoC’s impact on childbirth readiness is essential. Objective: Building on the introduction, this study aims to assess the effectiveness of the CoC model in improving childbirth readiness among third-trimester pregnant women. Materials and Methods: This study employed a quasi-experimental pretest–posttest design with a control group. The sample comprised 60 pregnant women in the third trimester, including 30 in the intervention group and 30 in the control group. The research instrument was a childbirth readiness questionnaire covering knowledge, emotional readiness, birth planning, social support, and physical preparedness. Data were analyzed using paired t-tests, independent t-tests, and effect-size analyses. Results: There was a significant increase in childbirth readiness scores in the intervention group after receiving CoC (from 60.2 to 85.6; p < 0.001). The control group did not show a significant improvement (p = 0.074). Independent t-test analysis revealed a significant difference between groups in posttest scores (p < 0.001). The effect size of 0.82 indicates a substantial impact of CoC on childbirth readiness. Conclusion: The CoC model is more effective than conventional antenatal care at enhancing childbirth readiness among third-trimester pregnant women.